Interspecific variation in the defensive responses of obligate plant-ants: experimental tests and consequences for herbivory - Bruna, E. M.; Lapola, D. M.; Vasconcelos, H. L. (Springer, 2004)
The aggressive behavior of ants that protect plants from herbivores in exchange for rewards such as shelter or food is thought to be an important form of biotic defense against herbivory, particularly in tropical systems. To date, however, no one has compared the defensive responses of different ant taxa associated with the same plant species, and attempted to relate these differences to longer-term efficacy of ant defense. We used experimental cues associated with herbivory-physical damage and extracts of chemical volatiles from leaf tissue-to compare the aggressive responses of two ant species obligately associated with the Amazonian myrmecophyte Tococa bullifera (Melastomataceae). We also conducted a colony removal experiment to quantify the level of resistance from herbivores provided to plants by each ant species. Our experiments demonstrate that some cues eliciting a strong response from one ant species elicited no response by the other. For cues that do elicit responses, the magnitude of these responses can vary interspecifically. These patterns were consistent with the level of resistance provided from herbivores to plants. The colony removal experiment showed that both ant species defend plants from herbivores: however, herbivory was higher on plants colonized by the less aggressive ant species. Our results add to the growing body of literature indicating defensive ant responses are stimulated by cues associated with herbivory. However, they also suggest the local and regional variation in the composition of potential partner taxa could influence the ecology and evolution of defensive mutualisms in ways that have previously remained unexplored.
Keywords: Azteca; Crematogaster laevis; myrmecophytes; mutualism; Tococa bullifera